Pengaruh Sistem Informasi Akuntansi dan Motivasi terhadap Kinerja Individu pada Sekolah Swasta di kota Palembang - Lionardi, Evelline Florencia; Sugara, Kathryn (Universitas Multi Data Palembang, 2024)
This research aims to analyze the influence of accounting and information systems as external and internal factors within an individual on that individual's performance in private schools in Palembang City. By using a quantitative research approach, the population of this study is. all 3,989 private school staff spread across each region of Palembang. The sample used purposive sampling. The analysis technique used in this research is a multiple linear regression approach (multiple regression) using SPSS version 26.00. The research results show that the accounting information system has no significant effect on individual performance in private schools in the city of Palembang. Motivation has a significant effect on individual performance in private schools in the city of Palembang and both accounting information systems and motivation simultaneously (together) also influence individual performance in private schools in the city of Palembang.